Studies on Polystyrene-Anchored Coordination Compounds of Divalent, Trivalent, Tetravalent and Hexavalent Metal Ions with the Schiff Base Obtained from the Condensation of 3-Formylsalicylic Acid and o-Hydroxyphenylurea - Kumar, D.; Syamal, A.; Pandey, V.; Rani, Mukesh (Asian Journal of Chemistry, 2011)
Chloromethylated polystyrene (PS-CH2Cl) reacts with 3-formylsalicylic acid and forms polystyrene 3-formylsalicylate. The nucleophilic addition reaction followed by elimination of one water molecule between polystyrene-3-formylsalicylate and o-hydroxyphenylurea in DMF in the presence of ethyl acetate results in the formation of polystyrene-anchored Schiff base, PSCH2- LH3 (1). Polystyrene-anchored coordination compounds, [PSCH2-LH2M(OAc)(DMF)] (2) (where M = Cu, Co), [PSCH2-LH2M'(OAc)(DMF)] (3) (here M' = Zn, Cd), [PSCH2- LH2M''(OAc)(DMF)3] (4) (M'' = Mn, Ni), [PSCH2-LH2FeCl2(DMF)2] (5), [PSCH2- LH2MoO2(acac)] (6) (acacH = pentane-2,4-dione), [PSCH2-LH2Zr(OH)3(DMF)2] (7) and [PSCH2- LH2UO2(OAc)(DMF)] (8) have been synthesized by refluxing a DMF swollen suspension of 1 and appropriate metal salts/compound. The polystyrene-anchored coordination compounds have been characterized on the basis of elemental analyses, spectral (IR, UV-VIS, ESR) and magnetic susceptibility measurement. 1 behaves as a monobasic bidentate ON donor ligand in these coordination compounds. [PSCH2-LH2M(OAc)(DMF)] (2) (M = Cu, Co) is square-planar and paramagnetic, [PSCH2-LH2M'(OAc)(DMF)] (3) (M' = Zn, Cd) is tetrahedral and diamagnetic. An octahedral geometry has been assigned to the paramagnetic compounds (4 and 5) and to the diamagnetic compounds (6 and 8). The coordination number of Zr is seven in 7. A pentagonalbipyramidal geometry has been assigned to the latter.